Vibration Monitoring Using Smart Data Node - Wong, Mun Lik (Universiti Sains Malaysia, 2014)
Vibration monitoring system for machine is important in engineering industry as to ensure that the machine is in good condition. Routine of the monitoring is to capture vibration data using sensor and process the data from time domain into frequency domain. Normally, every expensive machines such as chiller, automated manufacturing machine and motor-driven generator requires regular vibration monitoring service to make sure the machine is running at optimum performance without suffering from any damage. Nowadays, vibration monitoring systems are costly and require cumbersome analysis tools. Therefore, the objective of the project is to build an embedded system for vibration monitoring system at low cost and portable. This embedded system includes ADC model AD7606-4, Nuvoton NUC140-LB microcontroller board, and accelerometer. The input signal of the system is acquired from accelerometer and sampled by the ADC. The data is simulated by using MATLAB programming module in computer. The accuracy of the data captured is verified by comparing the simulation result in MATLAB with the result shown in oscilloscope. In conclusion, the primary objective of this project was achieved. The cost of building this system is RM583.30 which is 27% less than the development budget. Besides that, the secondary objective was also achieved with limitation. The benchmark of accuracy for this vibration monitoring system is 95%. The results have shown that the vibration monitoring system is accurate and consistent only for DC signal below -2V and above +2V and for the AC signal from 1Hz up to 600Hz.